EFFECTIVENESS OF Bacillus spp. IN CONTROLLING Fusarium sp. AND ITS EFFECT ON GROWTH AND PHYTOCHEMICAL OF SHALLOT (Allium ascalonicum L.) - Yuningsih Yuningsih; Yenny Wuryandari; Arika Purnawati (BRIN - Badan Riset dan Inovasi Nasional, 2026)
Shallot (Allium ascalonicum L.) is a key horticultural crop in Indonesia, but its productivity is constrained by moler disease caused by Fusarium sp. Chemical fungicides have limited effectiveness and raise environmental concerns, necessitating eco-friendly alternatives such as Bacillus spp. This study aimed to evaluate the potential of Bacillus spp. in suppressing moler disease and promoting shallot growth and resistance. A factorial Completely Randomized Design (CRD) was employed under in vitro and in vivo conditions, with two factors: Fusarium sp. inoculation (with and without) and Bacillus spp. treatments (control, Bcz 14, and Bcz 20). Results demonstrated that Bacillus spp., particularly isolate Bcz 20, significantly reduced disease intensity by up to 73.91% and delayed symptom development. Moreover, Bacillus spp. enhanced plant growth and induced the accumulation of flavonoids and saponins. These findings indicate that Bacillus spp. function as effective biological control agents and plant growth promoting rhizobacteria (PGPR), offering a sustainable strategy to improve shallot productivity while reducing reliance on chemical fungicides.